2022
DOI: 10.1038/s41598-022-15945-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of colonic dysmotility associated with autonomic dysfunction in patients with chronic refractory constipation

Abstract: We report the first study assessing human colon manometric features and their correlations with changes in autonomic functioning in patients with refractory chronic constipation prior to consideration of surgical intervention. High-resolution colonic manometry (HRCM) with simultaneous heart rate variability (HRV) was performed in 14 patients, and the resulting features were compared to healthy subjects. Patients were categorized into three groups that had normal, weak, or no high amplitude propagating pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…Our overall objective is to develop new treatments for patients with severe chronic colonic motility disorders, refractory to established treatments ( Rao et al, 2016 ; Camilleri et al, 2017 ; Chen and Huizinga, 2019 ). Our specific objective related to neuromodulation is to evaluate if sacral neuromodulation can relieve symptoms and restore autonomic dysfunction in these patients ( Liu et al, 2022 ). Patients with chronic constipation may not be able to generate spontaneous bowel movements.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our overall objective is to develop new treatments for patients with severe chronic colonic motility disorders, refractory to established treatments ( Rao et al, 2016 ; Camilleri et al, 2017 ; Chen and Huizinga, 2019 ). Our specific objective related to neuromodulation is to evaluate if sacral neuromodulation can relieve symptoms and restore autonomic dysfunction in these patients ( Liu et al, 2022 ). Patients with chronic constipation may not be able to generate spontaneous bowel movements.…”
Section: Introductionmentioning
confidence: 99%
“…HRV analysis is explored to evaluate autonomic functioning and dysfunction ( Shields, 2009 ; Huizinga et al, 2018 ; Barbier et al, 2022 ; Liu et al, 2022 ). We used HRV successfully to show that propulsive motor patterns generated by the human colon are associated with an increase in parasympathetic activity and a decrease in sympathetic activity ( Yuan et al, 2020 ; Ali et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As high sympathetic tone and impaired vagal pathway are implicated in the pathophysiology of IBS and constipation (Tanaka et al, 2008;Liu et al, 2022), it is reasonable to hypothesize that SDB is a potentially effective, complementary lifestyle management in patients with IBS. A previous study found that microvascular endothelial function of IBS patients improved following the SDB intervention (Katherine Jurek et al, 2022).…”
Section: Introductionmentioning
confidence: 99%